2007
DOI: 10.1038/sj.npp.1301422
|View full text |Cite
|
Sign up to set email alerts
|

Gene-by-Environment (Serotonin Transporter and Childhood Maltreatment) Interaction for Anxiety Sensitivity, an Intermediate Phenotype for Anxiety Disorders

Abstract: Anxiety sensitivity (AS) is a dispositional characteristic that predisposes to the development of anxiety disorders (eg, panic and posttraumatic stress disorder) and major depression. AS is subject to genetic and environmental influences, the former as yet unidentified and the latter known to include childhood maltreatment. The serotonin transporter gene (SLC6A4) promoter polymorphism (5-HTTLPR) has been associated with depression, but most consistently in the context of environmental stress. We tested the hyp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
148
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 204 publications
(159 citation statements)
references
References 56 publications
10
148
1
Order By: Relevance
“…Interestingly, previous research has found evidence to suggest that geneenvironment interactions are present in the development of anxiety sensitivity (Stein, Schork and Gelernter, 2008). Specifically, the effect of childhood maltreatment on anxiety sensitivity was found to be moderated by variation in the serotonin transporter gene (5HTTLPR).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, previous research has found evidence to suggest that geneenvironment interactions are present in the development of anxiety sensitivity (Stein, Schork and Gelernter, 2008). Specifically, the effect of childhood maltreatment on anxiety sensitivity was found to be moderated by variation in the serotonin transporter gene (5HTTLPR).…”
Section: Discussionmentioning
confidence: 99%
“…For example, although impulsive male individuals who are reared in protective environments are likely to exhibit only ADHD (Beauchaine, Hinshaw, & Pang, 2010;Beauchaine & McNulty, 2013), their impulsivity often progresses to more serious externalizing conduct if they are reared in high-risk environments characterized by coercive parenting (e.g., Patterson, DeGarmo, & Knutson, 2000), coercive and deviant peer group affiliations (e.g., Dishion & Hiatt Racer, 2013;Snyder et al, 2008), and neighborhood violence and criminality (e.g., Meier, Slutske, Arndt, & Cadoret, 2008). Similarly, environmental risk, including child maltreatment and exposure to protracted stress, increase the likelihood of emerging anxiety and depressive disorders among those with specific genetic vulnerabilities, such as the short allele of the serotonin transporter and certain glucocorticoid polymorphisms (see, e.g., Beauchaine, Crowell, & Hsiao, 2015;Nugent, Tyrka, Carpenter, & Price, 2011;Stein, Schork, & Gelernter, 2008). 2 …”
Section: Emotion Regulation Versus Emotion Dysregulationmentioning
confidence: 99%
“…A comparable gene by environment interaction involving the SLC6A4 gene that codes for the 5-HTT is apparent in the effects of childhood maltreatment on the risk for depression in humans (Caspi et al, 2003;Stein, Schork, & Gelernter, 2008).…”
mentioning
confidence: 99%